Composition of gastro-oesophageal refluxate. Issue 10 (October 1991) - Gotley, D C; Morgan, A P; Ball, D; Owen, R W; Cooper, M J
Abstract : Fifty two patients with abnormal acid gastro-oesophageal reflux were studied by simultaneous oesophageal pH monitoring and continuous aspiration for 16 hours. Aspirates (from discrete two hour periods) were analysed for volume, pH, bile acids (conjugated and unconjugated), trypsin, and pepsin. The results were compared with pH changes and degree of oesophagitis. Patients with oesophagitis had greater acid reflux than those without, but patients with stricture and Barrett's oesophagus had similar acid reflux to those with uncomplicated erosive oesophagitis. Pepsin concentrations were highest in patients with stricture and Barrett's oesophagus particularly during nocturnal periods. Conjugated bile acids were detected in 75% of patients, mainly during the night, but only 2% of aspirates contained concentrations likely to be cytotoxic. Unconjugated bile acids were not detected, and trypsin was seldom found. Reflux oesophagitis is caused by acid and pepsin. Bile acids and trypsin are probably unimportant.